Sustainability of internet usage: a study among malay youth in Kota Bharu, Kelantan - Ali Salman,; Mohd Yusof Hj. Abdullah,; Mohd Safar Hasim,; Latiffah Pawanteh, (2010)
This article discusses the issue of sustainability of internet usage. It is based on the study on Internet usage among Malay youths in Kota Bharu, Kelantan. The objectives of the study are to determine the factors which have positive and negative effects on sustainable usage of the Internet with respect to Malay youths and to identify the predictor factors for sustainability of Internet usage among Malay youths. This study is based on a model derived from diffusion of innovation theory, i.e. the innovation decision process model, by Rogers (2001). To determine sustainability, four variables were used viz. indispensability, relevance, gratification and beneficial. Six factors were used to measure their effects, either positive or negative, on sustainability of Internet usage. Communication channels, perceived and realized benefits and interpersonal and social network were the factors used to gauge positive effects on sustainability of Internet usage, while security concern and interruptions, moral issues and cost of maintenance and computer upgrade were used to gauge negative effects. This study used the survey research for obtaining data. Some 225 respondents were sampled from the Malays in Kota Bharu, Kelantan. They were interviewed using a standard questionnaire. Inferential statistics comprising multiple regression were used to analyse the data. The results of the study showed that Interpersonal and social network and perceived and realized benefits have significant positive effects on sustainability of Internet usage. The results also showed that issues relating to security concerns and interruptions have significant negative effect on the sustainability of Internet usage. Therefore, the factors which affect sustainability of usage should be given priority in the implementation of Internet and ICT related projects.